Oral candidiasis: Conventional and alternative treatment options - Vergani, C. E. [UNESP]; Sanitá, P. V. [UNESP]; Mima, E. G.O. [UNESP]; Pavarina, A. C. [UNESP]; Machado, A. L. [UNESP] (My University, 2013)
Candidiasis is a common opportunistic infection that affects mainly oropharyngeal and vaginal mucosa, but can also be an invasive systemic and life-threatening disease (candidemia). Nowadays, disseminated candidiasis is highly associated with mortality, especially in immunocompromised and hospitalized patients. Among all candidal infections, oral candidiasis is the most common form and affects especially denture wearers and severe ill patients, such as those infected by HIV virus, under antibiotic or chemotherapy, and submitted to organ transplantation. Additionally, candidiasis is of great clinical importance in patients with the systemic disease Diabetes Mellitus. Clinically, this superficial infection may be characterized as erythematous lesions or white patches and, despite the fact that oral candidiasis is frequently asymptomatic, patients may complain of slight bleeding and swelling in the involved area, mucosal burning or other painful sensations. Usually, candidiasis has been treated with topical or systemic antifungal agents, such as those belonging to polyenes (nystatin, anphotericin B) or azoles, which are divided into imidazoles (clotrimazole, miconazole, and ketoconazole) and triazoles (fluconazole and itraconazole). A new class of antifungals, the echinocandins (caspofungin, micafungin, and anidulafungin), is also clinically available. However, besides the side effects and high cost, the indiscriminate use of these agents, especially the azoles, has led to the development of fungal resistance. Although these antifungal drugs are aimed at treating the infection in the oral mucosa, it is widely known that strict oral hygiene and denture disinfection measures are crucial to the treatment of oral candidiasis. Thus, toovercome the limitations of these standard medications, the search for alternative therapies has directed the interest to physical methods of denture disinfection. In this context, the effectiveness of denture microwave disinfection has been demonstrated in several in vitro and in vivo studies. Another promising modality is the photodynamic therapy, which combines a photosensitizing agent with light of appropriate wavelength in the presence of oxygen, resulting in reactive species that are toxic to microbial cells. Moreover, immunotherapy, natural bioactive molecules, and vaccines have also been investigated. Based on the information given above, this book chapter will provide to the readers relevant and current scientific information about candidiasis. The topics that will be addressed are: oral candidal infection among healthy subjects, denture wearers, and immunocompromised patients; the frequent symptoms reported by infected individuals; and the available conventional and alternative treatment options for this common and clinically important disease.© 2013 Nova Science Publishers, Inc. All rights reserved.